The phase diagram of the MnTe–SnTe–Sb2Te3 ternary system and synthesis of the iso- and aliovalent cation-substituted solid solutions. (March 2022) - Orujlu, Elnur N.; Aliev, Ziya S.; Babanly, Mahammad B.
Abstract: The phase diagram of the MnTe–SnTe–Sb2 Te3 quasi-ternary system was studied and the new isovalent cation substituted Mn1- x Sn x Sb2 Te4 and Mn1- x Sn x Sb4 Te7 (x = 0 ÷ 1) solid solutions series were revealed along the aliovalent (Sb1-x-y Mnx Sny )2 Te3 and Sn1-x-y Mnx Sby Te (x = 0 ÷ 1) solid solutions. The phase relationships were established experimentally using differential thermal analysis (DTA), powder X-ray diffraction (PXRD), and scanning electron microscopy (SEM). The liquidus surface projection, an isothermal section at 500 °C, and the phase diagrams of the five isopleth sections have been constructed. Based on the obtained phase diagrams, the optimization of synthesis conditions was performed to approach the most rational design of the prepared solid solutions. The synthesized Mn1- x Sn x Sb2 Te4 and Mn1- x Sn x Sb4 Te7 solid solution phases were characterized and revealed that by increasing Sn content in both the solid solution series, the a - and c crystal lattice parameters increase linearly following Vegard's law. Highlights: The phase diagram of the MnTe–SnTe–Sb2 Te3 quasi-ternary system is constructed. New iso- and aliovalent cation-substituted solid solutions were synthesized via the investigation of the phase diagram. The crystal lattice parameters and homogeneity areas for the revealed solid solutions were determined.